State cooperative bank and rural development: a case study - Das, Debabrata (2002)
To achieve rural development in an economy, where geographical and other barriers are very strong, the people's participation and group efforts are preconditions, which can be ensured through cooperatives. Cooperatives have been regarded as the most desirable form of institutional credit for rural development from among all other sources of finance. In this paper a modest attempt has been made to evaluate the role played by the Arunachal Pradesh State Cooperative Apex Bank in the rural development of the State. - Reproduced.
Keywords: Case studies; Banks; Rural development